Sistem Kontrol Tinggi Muka Air Untuk Budidaya Padi - - Nurfaijah; Budi Indra Setiawan; Chusnul Arif; Slamet Widodo (Balai Teknik Irigasi, 2015)
This research aims to design a control system to keep the water level and soil moisture at a level that is suitable to the plant requirment and determines the optimum water level and soil moisture in each growth phase of paddy field cultivation. The water level control system was formed based on on-off controls system using Arduino Uno ATMega328P microcontroller. When the sensor gives input that the water level is below the set points, then microcontroller will command the irrigation valve to open and the drainage valve to close. The volume and time of irrigation and drainage control are dependent to set point. Set point was controlled based on water regime treatment. Water regime consisted of three treatments, which are wet regime (RB), slightly wet regime (RAB), and dry regime (RK). The research result showed that control system was very effective and efficient in controlling the water regime according to the control algorithms. Besides, the research result showed that the water regimes affected the plant growth, land productivity, and water productivity. Treatment of wet regime (RAB) gave the highest number of tiller (138 tillers), yield 194.7 g/hill (equal to 21 ton/ha with assumption of 30 cm x 30 cm spacing) and water productivity 3.16 kg/m3.